2011
DOI: 10.1123/jtpe.30.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions of Middle School Students Toward Competitive Activities in Physical Education

Abstract: The attitudes and perceptions of middle school students toward competitive activities in physical education were examined. Ten boys and 14 girls volunteered (11-high-skilled, 11 moderate-skilled, and 2 low skilled students) in 6th and 7th grade from a total of 6 schools, all offering competitive activities. Data collection was conducted over several months and included focus groups consisting of students of mixed skill levels, observations of competitive class activities, and informal interviews with teachers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 44 publications
1
55
0
15
Order By: Relevance
“…According to the TPB attitude, subjective norms, and perceived behavioral control leads to behavioral intention. In physical education, factors that have been shown to affect the development of attitudes include the teacher and the curriculum (Bernstein, Phillips, & Silverman, 2011;Carlson, 1995;Luke & Sinclair, 1991;Phillips & Silverman, 2012;Subramaniam & Silverman, 2000, 2002. It has not been determined if these factors also affect the development of students' attitudes toward fitness testing.…”
mentioning
confidence: 96%
“…According to the TPB attitude, subjective norms, and perceived behavioral control leads to behavioral intention. In physical education, factors that have been shown to affect the development of attitudes include the teacher and the curriculum (Bernstein, Phillips, & Silverman, 2011;Carlson, 1995;Luke & Sinclair, 1991;Phillips & Silverman, 2012;Subramaniam & Silverman, 2000, 2002. It has not been determined if these factors also affect the development of students' attitudes toward fitness testing.…”
mentioning
confidence: 96%
“…As Bernstein et al (2011) recently highlighted, the way that physical education teachers' structure competitive activities can affect the nature of the experience for the pupils. For that reason, encouraging the 'alternative' aspects of competition (O'Reilly et al, 2001) and focusing on a mastery climate (Bailey et al, 2009) may provide ways in which pupils can learn through competition and challenge the polarised nature of competition highlighted earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they noted that due to the fact that many pupils' conception of competition is winning and losing, the teacher rarely emphasised these alternative elements of competition. In a recent paper directly focused on pupils' perceptions on competition within physical education, Bernstein et al (2011) concluded that: (1) students of different skill levels perceived having fun in competitive activities differently; (2) pupils felt that having skill was a necessary part of competition although not everyone was developing their skills within competition; and (3) the structure of the various competitive activities influenced the student experience.…”
Section: Introductionmentioning
confidence: 97%
“…Several factors mentioned in the literature may contribute to the improvement of physical skills, such as time and appropriate practice (Escartí & Gutiérrez, 2001;Larson & Silverman, 2005), skill progression, and task presentation (Bernstein, Phillips, & Silverman, 2011;Ravizza & Stratton, 2007), and motivational climate (Quicke, 1999;Subramaniam & Silverman, 2002;Subramaniam & Silverman, 2007). Student athletes that did not perceive physical skill improvement responded that the teacher/coach was unsupportive and it affected the amount of time and energy that they devoted to their sport.…”
Section: Discussionmentioning
confidence: 99%